Clinical Applications of Nuclear Medicine Targeted Therapy (Springer International Publishing, 2018)
This book offers a practical and modern update on radioisotope therapy. Clinically oriented, it provides a thorough guide to patient management, with the latest indications and procedures for the current radioisotopic treatments. It addresses the clinical problems associated with each respective pathology, discussing the management of patients (diagnosis and non-radioisotope therapy), the radiopharmaceuticals available today, and the current radioisotopic procedures. Wherever possible, information on dosimetry is included at the end of each topic, together with a list of and comments on the most recent guidelines with their recommendations for radiometabolic therapy. The book is divided into six main sections: thyroid diseases, hepatic tumors (HCC and hepatic metastases), bone metastases from prostate cancer, lymphomas, and neuroendocrine tumors. The last section is dedicated to new perspectives of radioisotope treatment. Based on contributions from of a multidisciplinary team of specialists: oncologists, surgeons, endocrinologists, hematologists, urologists, radiopharmacists and nuclear medicine physicians, it provides a comprehensive analysis of the position of radioisotope treatments among the various therapeutic options. Readers interested in targeted therapy, radiometabolic therapy, radioimmunotherapy and radiometabolic imaging will find this book both informative and insightful.